Molecular Recognition and Transport of Active Pharmaceutical Ingredients on Anionic Calix[4]arene-Capped Silver Nanoparticles. (27th September 2012) - Perret, Florent; Tauran, Yannick; Suwinska, Kinga; Kim, Beomjoon; Chassain-Nely, Cyrielle; Boulet, Maxime; Coleman, Anthony W.
Abstract : A series of six anionic calix[4]arenes, having sulphonate, carboxylate, or phosphonate functions at either the para-aromatic position or the phenolic face were used to cap silver nanoparticles. Their molecular recognition properties were studied with regard to three active pharmaceutical ingredients, chlorhexidine, chloramphenicol, and. gentamycin sulfate. Of these APIs chlorhexidine is known to form cocrystals with the anionic calix[4]arenes, gentamicin sulfate is an aminoglycosidic antibiotic, and chloramphenicol is a neutral antibiotic. As expected the former two APIs show clear complexation behavior as demonstrated by shifts in the visible spectra whereas the last shows no modification in the wavelength of the plasmon resonance of the silver nanoparticles.